Impact of Spatial Hole Burning and Linewidth Enhancement Factor on Distributed-Feedback Quantum Cascade Lasers: A Comprehensive Design Analysis - Sara Zaminga; Lorenzo Columbo; Carlo Silvestri; Mariangela Gioannini; Frederic Grillot (IEEE Photonics Journal)
In this article, we use a time-domain traveling-wave approach with a coupled-mode theory to describe the dynamics of a mid-Infrared (MIR) Quantum Cascade Laser (QCL) in the Distributed-Feedback (DFB) configuration. We demonstrate that linewidth enhancement factor (LEF) and spatial hole burning (SHB) play a crucial role in influencing the device's single-mode behavior. Neglecting them leads to an overestimation of the interval of pump currents granting single-mode emission and to an inaccurate simulation of the QCLs' multimode dynamics. By taking into account these two mechanisms, we inspect the combined action of the DFB grating's coupling strength and end facets' reflectivity. The purpose is to supply designers with a guideline to achieve the optimal structure for efficient single-mode emission, which is a highly required specification in manifold applications, like free-space optical communication. Numerical simulations are in good agreement with experimental findings relative to a DFB QCL operating at 9.34 $μ$ m.